Epstein‐Barr virus‐negative extranodal "true" natural killer‐cell lymphoma harbouring a KDM6A mutation. Issue 1 (10th July 2017) - Tsuyama, Naoko; Asaka, Reimi; Dobashi, Akito; Baba, Satoko; Mishima, Yuko; Ueda, Kyoko; Oguchi, Masahiko; Tsuji, Hideki; Hatake, Kiyohiko; Takeuchi, Kengo
Abstract: Extranodal natural killer (NK)/T‐cell lymphoma, nasal type (ENKTL) is an extranodal aggressive T or NK‐cell lymphoma that is characteristically associated with Epstein‐Barr virus (EBV) infection and cytotoxic tissue‐destructive features. Although ENKTL is described as a distinct entity according to the 2008 WHO classification, a considerable complexity is associated with the differential diagnosis of other T‐cell lymphomas with respect to tumour cell origins, locations, and the presence of EBV infection, as well as molecular and cytogenetic abnormalities. Here, we report a rare case of EBV‐negative ENKTL, where the absence of EBV in the true NK‐lineage cells was confirmed by extensive phenotypic and genotypic analyses. Furthermore, using the next‐generation sequencing approach, we identified mutations in the tumour suppressor genes KDM6A and TP53 . The clinicopathological characteristics were almost similar to those of EBV‐positive ENKTL, except for the absence of EBV and histologically apparent angioinvasiveness. This is the first reported ENKTL case with mutations in the KDM6A gene. KDM6A is one of the histone‐modifying genes that are mutated in many human diseases including haematological cancers. Epigenetic regulation of gene expression has recently been demonstrated in ENKTL, and a similar pathway is thought to play an oncogenic role in EBV‐negative ENKTL. Our report shows the extent of comprehensive examination required before making a definitive diagnosis for NK‐ and T‐cell neoplasms and broadens the therapeutic options for potential targets.